Determinants of headquarters location and site selection for corporations listed on the Johannesburg stock exchange - Ramantswana, Thabelo (My University, 2019)
The location of headquarters presents an opportunity for economic growth in host countries and cities. The determinants of headquarters location and site selection vary in different contexts. Several studies have been conducted in Europe, USA, and recently in Asia documenting the dynamics of office/headquarters location. The variation in findings from different studies reinforces the importance of context. The African market in particular is under-researched, with little information available on the determinants of headquarters location and site selection. This research explored corporate headquarters (CHQs) location and site selection of companies publicly listed in the Johannesburg Stock Exchange (JSE) in South African metropolitan municipalities. This research explored and described CHQs location and site selection using both secondary and primary data. Location quotient and shift-share analysis was used to understand the competitiveness and specialisation of the metropolitan municipalities and the relationship with the concentration of CHQs. Then, interviews and a survey were undertaken to understand the determinants of CHQs location and site selection. Conjoint analysis, with a particular focus on the selfexplicated conjoint model, was used to understand the trade-offs that companies make when making location and site selection decision. The results indicated that South Africa’s cities’ historical development tends to influence the concentration of CHQs in certain metropolitan municipalities over others. However, in some instances, the competitiveness and/or specialisation explained the concentration. CHQs highly prefer locations that have developed telecommunication infrastructure and amenities, low operating costs, proximity to supporting industries and service providers, a skilled labour force, frequent and efficient local flights, favourable property taxes, tax incentives, and a favourable legal and regulatory framework. Regarding site selection, CHQs highly prefer facilities that have good security, energy efficiency, including backup generators, low operating costs, parking facilities, a flexible building interior, premises in good condition, access for the disabled, HVAC, good lease terms, and a reliable water supply. The findings of this study are beneficial to academics, government, and practitioners in the real estate market. This research helps to bridge the literature gap of headquarters research in the African context. It has open room for meaningful debate and engagement in the academic sphere in terms of unpacking the location and site selection decisions in the African context. The benefit to government is that the research uncovers the preferences of CHQs in location and site selection which can be used as guidelines to attract and retain headquarters. This affects the policy environment, the infrastructure and the general environment considered for headquarters to thrive. In today’s environment, gaining competitive advantage is crucial in industry. Considering the need for companies to be globally competitive, developers have to know the location and site determinants that matters most in real estate. Companies want the most desirable features when making headquarters location and site selection decisions. At the same time, developers and metropolitan municipalities, as well as other spheres of government, want to generate maximum benefits (profits, tax revenues, employment, and clients) from their investments in production and infrastructure developments where applicable. The findings provided the preference level of the determinants of CHQs location and site selection, which could help in the development of strategies to attract more CHQs to (South) Africa and to strengthen the competitiveness of the different metropolitan municipalities in fostering development and economic growth. The research also made a methodological contribution in that it adopted self-explicated conjoint analysis, which is predominately used in marketing. This study took a consumer behaviour approach in understanding the trade-offs that CHQs make in location and site selection decisions.
A thesis submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy Johannesburg, January 2019
Keywords: International business enterprises; Competition, International